Peer counselling as an approach to improve complementary feeding practices: a narrative review - Nabila Binte Haque; Seema Mihrshahi; Rukhsana Haider (BMC, 2023)
Abstract Background Appropriate complementary feeding can help reduce the risk of malnutrition and is especially important in Asian and African countries. Peer counselling has been used as an approach to improve complementary feeding practices and is often combined with other interventions, like food fortification or supplements, or as a part of broader nutrition education program. The aim of this narrative review is to assess the effectiveness of peer counselling on improving complementary feeding practices in Asian and African countries. Methods We searched through seven electronic databases: CINAHL, MEDLINE (OVID), PubMed, Embase, Web of Science, the Cochrane Library and WHO Global Health library from 2000 to April 2021, and had the following inclusion criteria. Studies were included if they were community- or hospital-based, had infants aged 5-24 months old, had individual or group peer counselling, and the effects of peer counselling on complementary feeding practices were measured. Methodological quality was assessed using the Joanna Briggs Institute's critical appraisal checklist for evidence studies. Results Out of 6 studies that met the above criteria, 3 studies were randomised controlled trials and 3 were quasi-experimental studies. In Bangladesh, India, Nepal and Somalia, peer counselling was found to be effective in improving timely initiation of complementary feeding, minimum meal frequency and minimum dietary diversity in all of our selected studies. In addition, improvement in breastfeeding practices, complementary foods preparation, hygiene, psychological stimulation for cognitive development of children and mothers' understanding of hunger cues were observed in some of our selected studies. Conclusions This review evaluates the effectiveness of peer counselling to improve complementary feeding practices in Asian and African countries. Peer counselling improves timely complementary feeding and ensures the correct proportions and consistency of foods including adequate amounts of food is given. Other important complementary feeding indicators like minimum dietary diversity, minimum meal frequency and minimum acceptable diet can also be increased through peer-counselling interventions. Peer counselling is well known to enhance the rate of breastfeeding practices, but this review suggests it is also effective for complementary feeding and may inform future nutrition programs to extend the length of peer counselling for mothers.